Urine‐based liquid biopsy in bladder cancer: Opportunities and challenges. Issue 1 (21st February 2023) - Wang, Gang; Jin, Wan; Xu, Zilin; Ju, Lingao; Shan, Danni; Li, Shenjuan; Yu, Mengxue; Cao, Xinyue; Liu, Nan; Qian, Kaiyu; Zhang, Yi; Xiao, Yu; et al.
Abstract: Bladder cancer (BLCA) is a most common urological tumours with high rate of recurrence, which needs long‐term of follow‐up. To date, diagnosis and surveillance of BLCA still rely on cystoscopy, an invasive and expensive method that increases the difficulty for routine follow‐up. Therefore, exploring new biomarkers or tests is an effective way to improve the current clinical management of BLCA. Recent years, liquid biopsy has received increasing attention, especially for its great potential for clinical application in the non‐invasive detection of tumours. In addition, liquid biopsy involves a wide range of biomarkers, including DNA, RNA, proteins, extracellular vesicles and metabolites in blood, urine or other body fluids. For BLCA, urine is a most ideal body fluid to achieve non‐invasive diagnosis and surveillance. Here, we address recent developments of urine‐based biomarkers or tests for clinical diagnostic challenges in BLCA, such as early detection, minimal residual, recurrence monitoring and therapeutic response. Meanwhile, the many challenges of urine biomarkers that need to be overcome are also discussed. Abstract : (1) Development of liquid biopsy has great potential of clinical application in non‐invasive detection of tumours. (2) Urine‐based biomarkers or tests for clinical management in bladder cancer can be widely used for early detection, minimal residual, recurrence monitoring and therapeutic response. (3) Many challenges need to be overcomed in the discovery and validation studies of urine biomarkers for bladder cancer.